EXTREMELY LOW BIRTH WEIGHT - LIFE QUALITY FOLLOW-UP - O.S. Yablon; D.Y. Vlasenko (Bukovynian State Medical University, 2019)
Follow-up of extremely low birth weight infants (<1000 g) at 18 months of corrected age with the definition of parameters of physical, psychomotor development and morbidity has made it possible to establish the incidence of poor outcomes (cerebral palsy, blindness, deafness, psychomotor retardation) among these children which amounted 59,2%. The main problems of "relatively healthy" children were iron deficiency and osteopenia states, nutritional difficulties and atopy.